Pengembangan Media Gerak Dakon Wayang untuk Meningkatkan Kemampuan Pemecahan Masalah FPB KPK Kelas 4 - Rahmanita Dwi Saputri; Asep Ardiyanto; Ervina Eka Subekti (STKIP Andi Matappa Pangkep, 2023)
This study aims to develop Gerak Dakon Wayang learning media on FPB KPK mathematics for grade IV, to improve students' problem-solving abilities and analyze the validity and suitability of learning media. The R&D method by Borg and Gall uses 6 steps; potentials and problems, data collection, product design, expert validation, design revision, and product testing. The subjects in this study are fourth grade at SDN Pajomblangan. Data were analyzed qualitatively from the results of interviews with teachers, students and quantitatively analyzed from the point of view of teachers, students, media experts, and material experts. The results of the study concluded that learning media complies with the Borg and Gall procedures to obtain criteria suitable for use. The media design uses a wooden box measuring which contains 40 small partitions equipped with tajo wayang as dakon seeds and material books and instructions for use. This media is valid and suitable for use in learning based on validation of media experts 90.59% and material experts 90%, analysis of the student responses is 96% and analysis of the teacher responses is 96.67%. Media improves students' problem-solving abilities based on pretest and posttest scores from the